Analysis of the absorbed constituents and mechanism of liquidambaris fructus extract on hepatocellular carcinoma - Wang, Shuai; Yang, Xin-Xin; Li, Tian-Jiao; Zhao, Lin; Bao, Yong-Rui; Meng, Xian-Sheng (Frontiers in Pharmacology, 2022)
Background: Hepatocellular carcinoma (HCC) refers to one of the top 10 cancers in terms of morbidity and mortality globally, seriously influencing people’s lives. First recorded in Compendium of Materia Medica, liquidambaris fructus (LF) generates definite anti-liver tumor effect. However, its effective substances and mechanism remain to be elucidated. Methods: Serum pharmacochemistry and UPLC-QTOF-MS technologies were employed to explore the plasma of rats after intragastric administration of liquidambaris fructus extract (LFE) in order to find the active ingredients. Subsequently, DEN-induced rat liver cancer model was established with the purpose of investigating the anti-tumor activity of LFE from physiological, pathological and biochemical aspects. Finally, non-target metabonomics combined with q-PCR and Western blot methods were adopted for revealing the mechanism. Results: Totally 11 prototype blood transfused ingredients, including imperatorin and phellopterin were detected. LFE presents excellent impact on enhancing the quality of life, prolonging the life cycle, reducing inflammatory reaction, protecting hepatocytes, improving body immunity and killing liver tumor cells. Altogether 82 endogenous differential metabolites were found in metabonomics, suggesting that LFE can treat HCC by acting on key targets of PTEN/PI3K/Akt pathway and fatty acid metabolism. Further research also verified that LFE can up-regulate the relative expression levels of PTEN, PDCD4, Caspase 9, Caspase 3, Bax and Bad as well as lower the relative expression levels of PI3K, AKT, VEGFA and Bcl-2. Conclusion: This study revealed the pharmacodynamic material basis of LFE in the treatment of HCC, and from the perspective of metabolomics proved that the effects of inhibiting the growth of tumor cells, promoting tumor cell apoptosis, reducing inflammatory reaction, protecting hepatocytes, improving the survival state of tumor rats, and prolonging the life cycle are related to its impact on PTEN/PI3K/Akt, fatty acid metabolism and other key signal pathways.